Penerapan Metode Design Thingking Pada Perancangan User Interface Aplikasi Kesehatan di The SEVEN GYM - Samudera, Elang; Nisa, Diana Aqidatun; Setiawan, Bayu (Innovative: Journal Of Social Science Research, 2024)
This study aims to design the user interface (UI) of a health application at The Seven Gym to promote users' physical and psychological balance. A qualitative approach was applied using the design thinking method, identifying user needs through the stages of empathize, define, ideate, prototype, and test. The study's findings show that a UI design incorporating sensory aspects, such as color and graphics, can enhance users' experience in tracking their health. The application is expected to motivate a healthier lifestyle overall, supporting physical health targets and mental well-being aligned with The Seven Gym vision and contributing to the goals of the sustainable development goals (SDGs).